EFEKTIFITAS MIKROORGANISME LOKAL (MOL) REBUNG BAMBU SEBAGAI AKTIVATOR PEMBUATAN KOMPOS TAHUN 2014 - Ali, Haidina; Kermelita, Deri (Journal of Nursing and Public Health, 2018)
Background : Maintenance and preservation of the environment can not be separated from some problems, such as environmental disruption caused by the use of fertilizers that contain chemicals. Another issue that is often complained of by the farmers are shortages of fertilizer. Subsidized fertilizer in Bengkulu city often experienced shortages caused by the allotment reduction come from central government. The purpose of the study was to determine the effectiveness of MOL as an alternative bamboo shoots in composting.Methods: The type of experimental research with only posttest design with control group design. With four treatments, namely the addition of a dose of 15 ml, 20 ml, 25 ml, 30 ml and four repetitions. Analysis of the data used univariate and bivariate analysis, followed by Bonferonni test.Results: no difference in the length of time composting with the addition of bamboo shoots MOL activator dose of 15 ml, 20 ml, 25 ml and 30 ml, with a dose of 30 ml was the most effective dose in accelerating the composting. Suggestion: expected for people to be able to utilize bamboo shoots as a new alternative in the making composting activator.